2008
DOI: 10.1364/ol.33.001783
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse reflectance spectroscopy with a self-calibrating fiber optic probe

Abstract: Calibration of the diffuse reflectance spectrum for instrument response and time-dependent fluctuation as well as interdevice variations is complicated, time consuming, and potentially inaccurate. We describe a novel fiber optic probe with a real-time self-calibration capability that can be used for tissue optical spectroscopy. The probe was tested in a number of liquid phantoms over a relevant range of tissue optical properties. Absorption and scattering coefficients are extracted with an average absolute err… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…However, for reflectance measurements, a spectral feedback measurement in combination with a sample measure has been shown to increase measurement precision. 40 When reviewing the calibration and quality control techniques in previous publications [40][41][42][43][44][45][46][47][48][49] that deal with fluorescence spectroscopy to generate excitation-emission matrices, it was found that the techniques discussed here offer equal or better management. For instance, the Raman peak of water can be used to identify one peak emission wavelength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for reflectance measurements, a spectral feedback measurement in combination with a sample measure has been shown to increase measurement precision. 40 When reviewing the calibration and quality control techniques in previous publications [40][41][42][43][44][45][46][47][48][49] that deal with fluorescence spectroscopy to generate excitation-emission matrices, it was found that the techniques discussed here offer equal or better management. For instance, the Raman peak of water can be used to identify one peak emission wavelength.…”
Section: Discussionmentioning
confidence: 99%
“…To ensure electrical safety, a hospital-grade isolation transformer with a 1000-W capacity ͑ILC-1000MED4, Shoreview, Minnesota͒ was used to reduce the leakage current to less than 40 A, a tenth of the standard hospital electrical safety limit, while the ground continuity was less than 210 m⍀, two-thirds of the maximum allowed. Thus, there was no electrical continuity to the fiber optic probe.…”
Section: Crd Performancementioning
confidence: 99%
“…The first step is to fit the wavelength dependent correction factors lCFD and lCFS. Let ˆ   be the average of the log of all the measurement at each wavelength, then we have 4 (2) with N ij = number of measurements for device i and standard j. At each wavelength  , put…”
Section: Model Estimationmentioning
confidence: 99%
“…We call the current generation of these devices Multispectral Digital Colposcope 3 (MDC3). Details may be found in [2][3][4]. One issue with with the MDC3 is that the shape and amplitude of the recorded spectra are different across devices for the same target.…”
Section: Introductionmentioning
confidence: 99%
“…30 Various source-collector geometries have been used to estimate the reduced scattering coefficient, μ 0 s , and the absorption coefficients, μ a , in DRS using a fiber optic probe. 23,29,[31][32][33][34] In general, the sampling volume increases as the source-collector separation increases. However, large sampling volumes are likely to be inhomogeneous.…”
Section: Introductionmentioning
confidence: 99%